Performance of tax investigations and tax sanctions for income concealment in Poland - Hybka, Małgorzta Magdalena (Skuteczność postępowań podatkowych i sankcji z tytułu nieujawniania dochodów do opodatkowania w Polsce, 2022)
This paper gives an insight into the application of one of the institutions of law adopted nearly twenty years ago by the government to counteract income tax evasion in Poland. The contents of the paper focusses on two main issues. First it enquires into the institution in question – in particular into its design, giving consideration both to the sources of information necessary to detect and disclose income concealment, standards of tax procedures and the legal framework behind them. In the course of this enquiry certain questions are asked and answered in relationship to the purpose, the effects, the sustainability of the regulations, that in its revised structure are in effect since 1st of January 2016, to the existing economic conditions. Secondly it determines the frequency and scope of the application of the procedures and provisions under consideration while taking into account the statistical data from the Ministry of Finance. It examines the results of tax investigations and evaluates their performance by using selected indicators. It also brings to light certain facts about the scale and nature of the phenomenon of income concealment in Poland.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2022; vol. 66, nr 3, s. 25-37
Keywords: concealment of income; tax evasion; tax sanctions; nieujawnianie dowodów; uchylanie się od opodatkowania; sankcje podatkowe